Influence of Gender, Body Mass Index, and Age on the Pharmacokinetics of Itraconazole in Healthy Subjects: Non-Compartmental Versus Compartmental Analysis - Miljković, Milijana N.; Rančić, Nemanja; Kovačević, Aleksandra; Cikota-Aleksić, Bojana; Skadrić, Ivan; Jaćević, Vesna; Mikov, Momir; Dragojević-Simić, Viktorija (Frontiers in Pharmacology, 2022)
Itraconazole is a triazole antifungal agent with highly variable pharmacokinetics, with not yet fully identified factors as the source of this variability. The aim of our study was to examine the influence of body mass index, gender and age on the first dose pharmacokinetics of itraconazole in healthy subjects, by using pharmacokinetics modeling, non-compartmental versus compartmental ones. Total of 114 itraconazole and hydroxy-itraconazole sets of plasma concentrations of healthy subjects of both genders, determined using a validated liquid chromatographic method with mass spectrometric detection (LC-MS), were obtained for pharmacokinetics analyses performed by computer program Kinetica 5®. Genetic polymorphism in CYP3A4, CYP3A5, CYP1A1, CYP2C9 and CYP2C19, were analyzed using PCR-based methods. Multiple linear regression analysis indicated that gender had significant effect on AUC, as the most important pharmacokinetics endpoint, while body mass index and age did not show such influence. Therefore, further analysis considered gender and indicated that both geometric mean values of itraconazole and hydroxy-itraconazole plasma concentrations in men were prominently higher than in women. Significant reduction of the geometric mean values of Cmax and AUC, as well as increment of Vd in females comparing with males was obtained. Analyzed genotypes and gender differences in drug pharmacokinetics could not be related. Non-compartmental and one-compartmental models complemented each other, while the application of the two-compartmental model showed a significant correlation with the analysis of one compartment. They indicated a significant influence of gender on itraconazole pharmacokinetics after administration of the single oral dose of the drug, given under fed conditions. Women were less exposed to itraconazole and hydroxy-itraconazole than man, due to a poorer absorption of itraconazole, its more intense pre-systemic metabolism, and higher distribution of both drug and its metabolite.